Origin of the Low Overpotential for Isopropanol Oxidation on Pt-Ru Electrocatalysts - Simanenko, Alexander; Samal, Pankaj Kumar; Hübsch, Robert; Škvára, Jan; Yang, Juntao; Kastenmeier, Maximilian; Winkler, Florian; Skála, Tomáš; Tsud, Nataliya; Mehl, Sascha; Mysliveček, Josef; Brummel, Olaf; et al. (ACS Energy Letters, 2024)
Electrochemically active liquid organic hydrogen carrier (EC-LOHC) technology is an emerging solution for safe and environmentally friendly hydrogen storage and energy conversion based on the use of organic redox-active compounds, such as the isopropanol/acetone couple. In this work, we identify the nature of the active state of the Pt-Ru electrocatalyst that provides the lowest overpotential and, thus, the highest catalytic activity. Toward this aim we employed ex situ electrochemical synchrotron radiation photoelectron spectroscopy (SRPES) and scanning tunneling microscopy (STM) in combination with in situ electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We show that the lowest overpotentials are not observed for Pt-Ru surface alloys but only in the presence of ultrasmall metallic Pt aggregates formed by dealloying of Pt-Ru catalysts upon oxidation and reduction cycles between 0.0 and 1.5 VRHE. By tuning the initial composition of the Pt-Ru surface alloy, we maximize the density of active Pt aggregates.
CRIS-Team Scopus Importer:2024-10-18